Production and characterization of highly transparent novel magneto-optical Ho2Zr2O7 ceramics with anion-deficient fluorite structures. (1st July 2023) - Hu, Liangbin; Lu, Bin; Xue, Bowen; Dai, Shixun
Highlights: Polycrystalline transparent Ho2 Zr2 O7 ceramics were successfully fabricated for the first time. The processing technology was optimized to achieve high optical quality. The optical and magneto-optical performances were investigated. The novel Ho2 Zr2 O7 ceramic materials exhibit potential application as magneto-optical elements. Abstract: Based on material design idea, we employ a co-precipitation strategy to obtain sinterable Ho2 Zr2 O7 fluorite particles, successfully leading to novel transparent Ho2 Zr2 O7 ceramics with good optical/magneto-optical properties. The resulting precipitation precursor is identified to be hydrated basic carbonate upon calcination at the optimum temperature of 1250 °C into near-spherical Ho2 Zr2 O7 nanopowder with an average size of ∼64 nm and unimodal narrow size distribution. The crystal intrinsic oxygen defect in fluorite ceramic generally exists in the form of F + center. The best bulk specimen achieved in this work exhibits a high refractive index of ∼2.1 and a high transparency of ∼74.4% at 1000 nm comparable with the corresponding defect-free single crystal (∼76.4% in theory). In the Ho2 Zr2 O7 structure system, the electronic polarizability of O 2− anion generally remains constant around 2.2 Å 3 in the visible region and the corresponding optical basicity is approximately 0.9. The developed magneto-optical transparent Ho2 Zr2 O7 ceramic has Verdet constants of -180 ± 3, -157 ± 5, -87 ± 2, -54 ± 2, and -43 ± 2 rad T −1  m −1 at 515, 635, 780, 980, and 1064 nm, respectively, which are roughly 1.2-fold higher than the commercial TGG crystal.